Will jellyfish rule the world? a book about climate change - Hickman, Leo (Puffin Books, 2009)
Will Jellyfish Rule the World? breaks down the causes and effects of climate change in a fresh, fun and easy-to-follow format. Packed with practical everyday things we can all do right now to make a difference